Apparent shifts in the microplankton community in response to zinc and iron enrichments in the Northeastern Subarctic Pacific - Crawford, David W.; Purdie, Duncan A.; Lohan, Maeve C.; Statham, Peter J.; Peterson, Tawnya D.; Kennedy, Hilary A.; Lipsen, Michael S.; Putland, Jennifer N.; Whitney, Frank A. (Frontiers in Marine Science, 2022)
The offshore Gulf of Alaska—in the northeastern subarctic Pacific—is a high-nitrate, low-chlorophyll (HNLC) oceanic region where concentrations of dissolved iron (DFe) and zinc (DZn) are of the order ~0.1 nmol kg−1 in surface waters. At the average winter mixed layer depth of ~120 m, DFe and DZn are of the orders ~0.1–0.2 nmol kg−1 and ~1–2 nmol kg−1, respectively. Vertical supply of Fe to surface waters is therefore limited, with phytoplankton blooms driven by episodic atmospheric and lateral inputs of Fe. In contrast, DZn is presumably replenished through seasonal vertical mixing, though maintained at low levels in surface waters, even in winter, implying that removal processes are in operation. Previous supplementation experiments have demonstrated that phytoplankton biomass (chl-a), growth, and drawdown of nitrate (NO3-) are stimulated strongly by Fe but only minimally, if at all, by Zn alone. Using on-deck bioassay incubations of surface waters, we confirm that the addition of Fe stimulates significant increases in chl-a and large diatoms, and drawdown of NO3- and silicic acid [Si(OH)4]. Associated drawdown of DZn and dissolved cadmium (DCd) indicated Zn stress in the control and +Fe treatment. Supplementation with Zn alone had no significant impact on NO3- and commonly monitored pigments such as chl-a and fucoxanthin. However, in the +Zn treatment, DFe and coccolithophore abundance were significantly lower, and the concentration of particulate organic carbon (POC) and that of the pigments alloxanthin and chlorophyll c1+2 were significantly higher than those in control incubations. Our experiment corroborates previously observed relationships between DZn and alloxanthin and chlorophyll c across the subarctic north Pacific and Bering Sea and could help to explain the low or undetectable concentrations of alloxanthin frequently observed in this region. Alloxanthin is a pigment specific to the cryptophytes, either within free-living cells or within functional plastids retained by mixotrophic protists. Both cryptophytes and mixotrophic ciliates, such as Laboea sp. and Strombidium spp., make a variable but significant contribution to phytoplankton biomass in this area. In the absence of Fe supply to surface waters, Zn could play a hitherto unsuspected role in shaping plankton communities in the HNLC Gulf of Alaska.